Suppression of extracellular invertase inhibitor gene expression improves seed weight in soybean (Glycine max) - Tang, Xiaofei; Su, Tao; Wei, Hongbin; Du, Yejie; Greiner, Steffen; Rausch, Thomas (The journal of experimental botany, 2017)
Highlight. The roles of GmCIF1 and GmC/VIF1 as invertase inhibitors were examined in vitro in soybean (Glycine max), and post-translational elevation of extrac